Implicações da pandemia de COVID-19 na segurança alimentar e nutricional dos escolares de 6 a 10 anos de idade do município de Realeza - Paraná - Borsa, Mayara Pryscila (2023)
In Brazil, the COVID-19 pandemic has generated considerable economic and public health crises. The school is an environment that encourages the promotion and improvement of health and healthy eating habits, and the PNAE was inserted in the school environment, becoming a public policy with the objective of collaborating with the biopsychosocial development, learning, school performance and the formation of students' healthy eating habits, through food and nutrition education (EAN) actions and the provision of meals that meet nutritional needs, during the school period. Due to the pandemic, schools were closed at the beginning of 2020, and classes were held remotely, therefore, students did not have access to school meals within the institutions. This mixed approach, descriptive, analytical and documentary study, in which primary data was collected (quantitative stage) and document analysis (qualitative stage), was carried out in 8 municipal public schools, with the objective of evaluating the implications of the pandemic. of COVID-19 on food and nutrition security (SAN) of schoolchildren aged 6 to 10 years in the municipality of Realeza, State of Paraná. A total of 882 students participated in the study, of which 535 (61%) had a body weight considered normal for their age, being classified as eutrophic. In the year 2022, the rates of overweight and obesity (36%) and thinness (2%) increased compared to previous years (2017 to 2020) and the statistical analysis showed significance between the years and the results of nutritional assessments. Regarding the EBIA food insecurity questionnaire, 337 (62.4%) of the students' family members were food insecure and 203 (37.6%) had some type of food insecurity, among these, 26 families are in a serious situation of food insecurity. The research also analyzed official federal, state and municipal documents, through which one can verify the measures taken with regard to the FNS of students during the pandemic period. These analyzes indicated that it is necessary to implement effective public policies at all levels of government spheres to combat cases of food insecurity in the population. In summary, the survey revealed that 203 families had some type of food insecurity and that there was an increase in cases of thinness, overweight and obesity, compared to previous years.